Determinants of adoption of agricultural innovations and profitability of cereals and legumes in the Sudan savanna of Nigeria - Ayanwale, A.B.; Abdoulaye, Tahirou; Kamara, A.; Adekunle, A.; Fatunbi, O.; Ayedun, B.; Akinola, Adebayo A. (2014)
In order to facilitate a scientific assessment of the viability of the IAR4D concept, this paper analyzed the factors affecting adoption of agricultural technologies as well as determined the profitability of cereals and legumes in the Sudan savanna of Nigeria. Data were obtained from the baseline study conducted in 2008 as well as other official secondary data. Descriptive statistics, budgetary as well as logistic regression techniques were used to analyze the data. Results show that the respondent's age range vary between 40 and 55 years implying that they are relatively young elders with large family size of between 12 and 14 possibly providing family labour for farm work. The educational level is expectedly low with only about a third of them having up to six years of formal education. The regression results reveal that the location of the farmer, large family size and awareness encouraged adoption of new technologies across the various sites. The gross margin analysis reveals that among the cereal crops, maize gave the highest yield and revenue, while for legume crops, groundnut gave the highest yield and revenue figures in all sites with labour being the highest variable cost item on all sites. In conclusion, the study affirmed that farmers in the study area possess the potential to adopt agricultural innovations which could increase yields and enhanced income.